Confining Flat Ru Islands into TiO2 Lattice with the Coexisting Ru–O–Ti and Ru–Ti Bonds for Ultra‐Stable Hydrogen Evolution at Amperometric Current Density and Hydrogen Oxidation at High Potential - Luyun Chen; Chunlei Li; Mengling Liu; Ziruo Dai; Haibin Wang; Xuan Zhou; Qiuping Zhao; Yuanyuan Cong (Advanced Science)
Abstract Effective hydrogen evolution reaction (HER) under high current density and enhanced hydrogen oxidation reaction (HOR) over a wide potential range remain challenges for Ru‐based electrocatalysts because its strong affinity to the adsorbed hydroxyl (OHad) inhibits the supply of the adsorbed hydrogen (Had). Herein, the coexisting Ru─O─Ti and Ru─Ti bonds are constructed by taking TiO2 crystal confined flat‐Ru clusters (F‐Ru@TiO2) to cope with above‐mentioned obstacles. The different electronegativity (χTi = 1.54 < χRu = 2.20< χO = 3.44) can endow Ti in Ru─O─Ti bonds with more positive charge and stabilize Ru of Ru–Ti bonds with the low‐valence. The strength of Ru─OHad is then weakened by the oxophilicity of positively charged Ti in Ru─O─Ti bonds and the stronger Ti─OHad bond could release active Ru, especially for low‐valence Ru in Ru─Ti bonds, to serve as exclusive Had sites. As expected, F─TiRu@TiO2 shows a low HER overpotential of 74 mV at 1000 mA cm−2 and an ultrahigh mass activity (j0,m) of 3155 A gRu−1 for HOR. More importantly, F─Ru@TiO2 can tolerate the HER current density of 1000 mA cm−2 for 100 h and the high anodic potential for HOR up to 0.5 V versus RHE.